'n Kritiese evaluering van die sertifikaatprogram in musiek by die Universiteit Stellenbosch - Schutte, Charla Helena (Stellenbosch : Stellenbosch University, 2012)
Some digitised pages may appear illegible due to the condition of the original hard copy. (entire content of poor quality)